SELF-EDUCATION AS A BASIS OF PROFESSIONAL SELF-DEVELOPMENT PERSONALITIES OF THE FUTURE TEACHER - Dereza І.С. (Pedagogy of Higher and Secondary Education, 2022)
In the article are disclosed self-education as the basis of professional self-development of the person of the future teacher.